Research on the electrical conductivity and mechanical properties of copper slag multiphase nano-modified electrically conductive cementitious composite. (11th July 2022) - Ren, Zhenhua; Sun, Junbo; Zeng, Xiantao; Chen, Xi; Wang, Yufei; Tang, Weichen; Wang, Xiangyu
Highlights: Nano-graphite as a functional filler incorporated into concrete can significantly improve its electrical conductivity. Meanwhile, the proper amount of nano-graphite addition can also increase its mechanical strength. The addition of copper slag improved the mechanical properties and electrical conductivity of ECCC. The chemical activation improved the reactivity of the volcanic ash in the fly ash–cement system. The ultrasonic vibration process facilitates the uniform distribution of nano-graphite. Combined activation is the best method to improve mechanical properties and electrical conductivity, possessing the advantages of chemical and ultrasonic activation. Abstract: Electrically conductive cementitious composite (ECCC) features structural material functions, electrical conductivity, and piezoresistivity properties broadly applied in snow melting, electromagnetic shielding, cathodic protection system, and structural health monitoring (SHM). Nano-graphite is an ideal ECCC functional filler since its ability to fill molecular pores, reduce concrete shrinkage and significantly improve their electrical conductivity. However, nano-graphite is high-cost and its excessive amounts can lead to particle agglomeration. Therefore, copper slag (CS) can partially replace NG to beneficially reuse the waste by-products and save energy for protecting the environment. Nevertheless, a single blend of fillers hardly exploits the potential mechanical and conductive properties. Consequently, different activation methods were adopted to obtain desirable dispersion and performances. This paper explored the influences of chemical alkali excitation, ultrasonic vibration, and combined activation on copper slag and nano-graphite wrapped ECCC. Experimental results from a total of 387 ECCC specimens with 16 design ratios demonstrated that the combined treatment of alkali excitation and ultrasonic vibration was superior to any single treatment. The optimal samples based on 3 wt% ratio of NG and 60 wt% of copper slag activated with combined treatment exhibited 44.55 MPa compressive strength, 6.65 MPa flexural strength, and 8180 Ω·cm electrical resistance. Lastly, an SEM was conducted to analyze the microstructure of the mixture and ECCC and a schematic diagram was proposed.